2019
DOI: 10.1155/2019/9172607
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Kidney Function in Tenofovir Disoproxil Fumarate Based Regimen and Associated Factors: A Hospital Based Prospective Observational Study in Ethiopian Patients

Abstract: Purpose. Tenofovir disoproxil fumarate (TDF), a drug broadly used in combination antiretroviral therapy, is associated with renal dysfunction but the prevalence varied from country to country and it is not known in Ethiopia. The objectives of this study were to assess the prevalence of renal dysfunction and risk factors associated with it and the mean change in estimated glomerular filtration rate in human immunodeficiency virus infected patients receiving TDF based antiretroviral regimen at Tikur Anbessa Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 44 publications
6
12
0
Order By: Relevance
“…Compared with patients aged 20-29 years, patients with ages equal to and greater than 60 years were more likely to report renal impairment. is finding was in agreement with studies conducted in Ethiopia [25] and Malaysia [10], which showed that old age was considered to be a risk factor for TDF induced nephrotoxicity. It is known that kidney function and structure would deteriorate by age [25,32].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Compared with patients aged 20-29 years, patients with ages equal to and greater than 60 years were more likely to report renal impairment. is finding was in agreement with studies conducted in Ethiopia [25] and Malaysia [10], which showed that old age was considered to be a risk factor for TDF induced nephrotoxicity. It is known that kidney function and structure would deteriorate by age [25,32].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we also found that patients who had low BMI were significantly associated with renal impairment compared with those who had normal BMI; this result was similar to studies conducted in Vietnam and Japan [9,28,29], but in contrast to the study conducted in Ethiopia [25]. It may be different sample sizes [25], duration of study time, as a little is known about BMI effect on renal function on the long term [9]; therefore, the need for deep and longterm research should be taken into account.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations